Tax-Deductible Provisions for Gluten-Free Diet in Canada Compared with Systems for Gluten-Free Diet Coverage Available in Various Countries - Maria Ines Pinto-Sanchez (Canadian Journal of Gastroenterology and Hepatology, 2015)
Celiac disease affects 1% of the North American population, with an estimated 350,000 Canadians diagnosed with this condition. The disease is triggered by the ingestion of gluten, and a lifelong, strict gluten-free diet (GFD) is the only currently available treatment. Compliance with a strict GFD is essential not only for intestinal mucosal recovery and alleviation of symptoms, but also for the prevention of complications such as anemia, osteoporotic fractures and small bowel lymphoma. However, a GFD is difficult to follow, socially inconvenient and expensive. Different approaches, such as tax reduction, cash transfer, food provision, prescription and subsidy, have been used to reduce the additional costs of the GFD to patients with celiac disease. The current review showed that the systems in place exhibit particular advantages and disadvantages in relation to promoting uptake and compliance with GFD. The tax offset system used in Canada for GFD coverage takes the form of a reimbursement of a cost previously incurred. Hence, the program does not help celiac patients meet the incremental cost of the GFD – it simply provides some future refund of that cost. An ideal balanced approach would involve subsidizing gluten-free products through controlled vouchers or direct food provision to those who most need it, independently of ‘ability or willingness to pay’. Moreover, if the cost of such a program is inhibitive, the value of the benefits could be made taxable to ensure that any patient contribution, in terms of additional taxation, is directly related to ability to pay. The limited coverage of GFD in Canada is concerning. There is an unmet need for GFD among celiac patients in Canada. More efforts are required by the Canadian medical community and the Canadian Celiac Association to act as agents in identifying ways of improving resource allocation in celiac disease.